REFORMULATION OF LEARNING AND TEACHING HISTORY AT ELEMENTARY AND SECONDARY LEVEL OF EDUCATION - Anas, Zulfikri (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
Past, present, and future are continuous processes of life. However, as people are not able to look clearly into the future, but they have to prevent to make a same mistake, people must learn history appropriately.Since the phenomenon of life goes through uninterrupted processes, people should be able to predict the future by dealing with past-to-present happenings wisely. This is called â€œhistorical competenciesâ€. The focus of learning and teaching history is to make students able to appreciate the journey of life in the context of historical education so that they are able to build a better future, individually or within a community or a country in responsible manners. To acquire the ability, learning and teaching process of history should be reformulated by organizing materials in the curriculum, textbooks, and learning and teaching strategies. In this moment, history is â€œthe centerâ€ of social science education, as implemented in several developed countries. Each social science subject is oriented to create an understanding about historical development of particular countries with the intention that students are able to appreciate it. Therefore, they will be encouraged to be good citizens and responsible for granting a better future for the next generation. Furthermore, this reformulation will make history courses more valuable to create a better life in the forthcoming.